STUDENTS’ PERCEPTIONS ON THE LAYOUT OF STRESS-FREE PRESENTATIONS WEBSITE - Anis Idayu Aziz,; Wan Nazihah Wan Mohamed,; Nor Hairunnisa Mohammad Nor, (Journal of Islamic, Social, Economics and Development, 2024)
The landscape of education has undergone a remarkable transformation with the emergence of e-learning platforms and tools. Computer softwares using learning management systems have allowed students to interact with their teachers. Although traditional classroom setting is still valuable, it has limitations in terms of time, location, and individualised attention. One of the skills students need to master in their learning years is the ability to excel in oral presentation. Conducting English presentations is a true challenge especially among Malay students who use English as their second language. This study focused on students’ insight on the use of Stress-free Presentation website with the aim to enhance students’ presentation skills. To ensure that the development of Stress-free Presentations website is an effective teaching and learning tool in increasing students’ presentation skills, identifying the students’ perception of the website is crucial. For the purpose of data collection, a set of online questionnaire consisting of adapted items was utilized to measure the perception of the respondents towards Stress-Free Presentation website. The population for this study consisted of 258 undergraduate students who registered for Oral Presentation course at Universiti Teknologi MARA (UiTM) Kelantan Campus. The questionnaire was distributed using a Google Form through the class WhatsApp messaging group. Once the data were gathered from the respondents, the statistical package for social sciences (SPSS) version 23 was utilised to conduct the test for descriptive analysis of the study. The findings indicate that the website displays eye pleasing text, has suitable text length and applicable multimedia visual aids with well-organised and related contents as well as interesting resources. It also proves that website learning could supplement the resources for traditional classroom and simultaneously engage students in interactive learning experiences at their own pace and convenience.